1995
DOI: 10.1002/ijc.2910600116
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA content and chromatin texture in multidrug‐resistant human leukemic cell lines

Abstract: Nuclear morphological alterations associated with multidrug resistance (MDR) were evaluated by image cytometry in various human leukemic cell sub-lines: 3 cell lines with P-gp-mediated resistance (CEM-VLB, HL60/Vinc, K562-Dox), the non-Pgp-mediated MDR HL60/AR leukemic cell line with over-expression of MRP, and the at-MDR CEM-VMI leukemic cell line with alteration of topoisomerase II. All these MDR cell sub-lines were obtained by drug selection and were compared with their sensitive counterparts and with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…6 Nuclear chromatin pattern has been reported to be changed in drug-selected human MDR cells and not in other MDR cells without drug selection. 27 However, the ALLm patients in this study were not exposed to any chemotherapeutic drugs before and no ALLm cases showed Pgp expression before induction chemotherapy by immunohistochemistry. This result suggests that the difference of ALLm from ALLt is not due to Pgp expression.…”
Section: Discussionmentioning
confidence: 72%
“…6 Nuclear chromatin pattern has been reported to be changed in drug-selected human MDR cells and not in other MDR cells without drug selection. 27 However, the ALLm patients in this study were not exposed to any chemotherapeutic drugs before and no ALLm cases showed Pgp expression before induction chemotherapy by immunohistochemistry. This result suggests that the difference of ALLm from ALLt is not due to Pgp expression.…”
Section: Discussionmentioning
confidence: 72%
“…Protein kinase inhibitors can change the cellular metabolism considerably. As toxic drugs they can initiate endoplasmic reticulum stress response via the expression of proteins such as chaperones and heat shock proteins to alleviate the adverse effects [39]. The proteome of the resistant cells change as a result.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the changes in the intensities of the bands at 1239 and 970 cm À1 for the imatinib resistant cells indicate structural changes in nuclear morphology, organization, and architecture such as alterations in the nuclear/ cytoplasmic ratio, hyperchromacity, chromatin aggregation and changes in DNA condensation between imatinib sensitive and resistant K562 cells. Multidrug resistance was linked to specific nuclear morphological changes acquired in the process of selection by cytotoxic drugs rather than P-gp overexpression or changes in the expression level of topoisomerase II beta [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen parameters were computed from each nuclear image: three morphometric features (nuclear area NA, nuclear perimeter NP, and form factor FF), one densitometric (integrated optical density IOD), and nine textural parameters. The distribution of nuclei according to DNA-IOD was plotted to provide cell cycle distribution and the margins defining G 0 G 1 and G 2 peaks were defined as modal IOD ± 15% as previously described (2). At least 100 reference cells (mouse hepatocytes) were measured in the same conditions for the calibration of the normal diploid (2c) value.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in cell lines derived from various tissues (lung, ovary, breast), we and others reported that this drug resistance was associated with alterations in nuclear architecture that could impact epigenetic ABCB1 gene control (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 91%